2016
DOI: 10.1002/hed.24637
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising hyalinizing clear cell carcinoma: A population‐based study with molecular confirmation

Abstract: Molecularly confirmed HCCC accounted for 2.5% of salivary gland malignancies at our institution. HCCCs are indolent tumors with a propensity for locoregional recurrence. © 2016 Wiley Periodicals, Inc. Head Neck 39: 503-511, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 54 publications
4
31
1
1
Order By: Relevance
“…2,19,20 Recent cases of CCA have been documented in all regions of the head and neck. 1-8,14-17 Our findings corroborated these data. Although a great proportion of tumors presented in the major salivary glands (37%) in our study, most tumors arose from other regions in the head and neck, particularly in the oral cavity and pharynx.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2,19,20 Recent cases of CCA have been documented in all regions of the head and neck. 1-8,14-17 Our findings corroborated these data. Although a great proportion of tumors presented in the major salivary glands (37%) in our study, most tumors arose from other regions in the head and neck, particularly in the oral cavity and pharynx.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, these concomitant medical comorbidities may preclude patients from surgical interventions, contributing to worse prognosis. Women and men were affected at a nearly equal rate (0.92:1), a finding that is in contrast with the studies by Hernandez-Prera et al 17 and O’Sullivan-Mejia et al 18 that found female predominance (1.57:1 and 2.67:1, respectively).…”
Section: Discussioncontrasting
confidence: 66%
“…The most common site of involvement is the base of tongue but other minor salivary glands of the oral cavity, such as the palatal mucosa, floor of mouth, and buccal mucosa, can be involved. Although CCC can occasionally show locoregional and even distant metastasis, it is generally considered an indolent tumor with a good prognosis …”
Section: Malignant Neoplasmsmentioning
confidence: 99%
“…Although CCC can occasionally show locoregional and even distant metastasis, it is generally considered an indolent tumor with a good prognosis. 102,143,144 Where described in the literature, CCCs are well-defined with occasional calcifications or focal necrosis. 145,146 These lesions demonstrated only mild irregular enhancement on CT 146 with hypointense T1 signal and heterogeneously isointense T2 signal.…”
Section: Clear Cell Carcinomamentioning
confidence: 99%
“…Em um estudo mais focado nessa lesão, Milchgrub et al(4), descreveram uma série de casos, enfatizando algumas características histológicas da lesão como a distribuição das células e seu estroma hialino, além de traçar um perfil imunohistoquímico característico. (4) Nesse artigo, a lesão de células claras foi chamada pela primeira vez de carcinoma de células claras hialinizante de glândulas salivares (1,7,8). Mesmo após isso a lesão não foi aceita diretamente pela OMS e só chegou a ser reconhecida como Carcinoma de células claras de glândulas salivares na última classificação de 2017.…”
unclassified